Complexity of Spatiotemporal Synchronization Activity of GaussianMap through Random Link - Sarkar, Jayanta Kumar; Khan, Mohammad Ali; Das, Barun (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study spatiotemporal synchronization activity (STSA) of coupled Gaussian maps in a complex network. Our complex networks are changed stochastically with time. A coupled map lattice (CML) is adopted in Gaussian map as a prototype of a spatiotemporal chaotic systems with variation of parameters. A key motivation is that to determine (i) the effects of variation of randomness, (ii) the effects of variation of coupling strength ε , (iii) the effects of variation of parameter α when β is fixed and (iv) the effects of variation of β when parameter α is fixed on the synchronization behaviour. The variation of the basin size with respect to rewiring probability for different coupling strength and basin size with respect to coupling strength ε for different randomness, different parameters α and β are also plotted.